A violência desde o prefácio de Jean-Paul Sartre para Os condenados da terra de Frantz Fanon - Lima, Paulo Willame Araújo de (2020)
This research considers violence as an important philosophical problem for the ethical and political field, especially when it comes to colonial violence. The objective here is, therefore, to know in what sense the violence appears as a philosophical problem of ethical and political character. Jean-Paul Sartre's (1905 - 1980) preface to the book The Damned of the Land, by Frantz Fanon, a philosopher from Martinique, with African descent, but also in dialogue with much of the sartrean work, has as its central text. Thus, this work starts from the hypothesis that there is an completeness in sartrean thought in which the main philosophical object of study is man and his intersubjective and worldly relations. Starting from the understanding that there is a sartrean writing methodology coherent with all its philosophical-literary production, this text is organized in three sessions to define the central concepts of research on human reality as a philosophical category, since man is the being for whom violence - an instrument of radical denial - comes into the world. In this way, the theme is developed through methodological questions directed to the preface studied, namely: 1) what is the preface in the context in which it appears ?; 2) why the effort to write the preface to a book by a black author that was directed to his brothers in the struggle against colonization ?; 3) for whom does Sartre write the preface ?. In this way, the research reaches its refinement by critically presenting the four moments of violence exposed by the philosopher in the preface, namely: 1) The original violence that establishes oppression; 2) the hatred of the oppressed against themselves characterized by revolt; 3) irrepressible violence against the oppressor that manifests itself as resistance; and 4) the man who needs to violently get rid of the oppressor that he himself has become, towards the permanent revolution of the authentic man. Finally, it seeks to elucidate the phenomenon of violence in its instrumental and not, a priori, evaluative function, then realizing the potentialities and limitations of violence mainly in the ethical and political spheres against any oppressive system.